Pengaruh Konsentrasi Natrium Nitrat dan Natrium Dehidrogen Fosfat pada Media Walne Terhadap Konsentrasi Biomassa dan Protein Nannochloropsis oculata - Dedi Widnyana Dinata, Kadek; Dewi Anggreni, Anak Agung Made; Semadi Antara, Nyoman (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 1 (2017): Maret)
This study aims to know the  effect of concentration of Sodium Nitrate  (NaNO3) and Sodium Dehidrogen Phosphate  (NaH2PO4) on walne media on the biomass concentration and protein Nannochloropsis oculata and determine the best concentration of NaNO3  and NaH2PO4  on the Walne media to produce Nannochloropsis oculata biomass with highest protein content. This study was designed with a randomized block design with two factors, each treatment was divided into two by the time of cultivation.The data obtained were analyzed by Anova, if there was  a real effect will be followed by Duncan test. The results showed that the concentration of NaNO3  and NaH2PO4  on media Walne had significant effect on the concentration of the Nannochloropsis oculatamicroalgae biomass and protein content, and no interaction of both factors.The concentration of NaNO3  of 200 g/L and NaH2PO4  of 25 g/L at Walne media producethe hight biomass concentration of Nannochloropsis oculata biomass amount of 7.66 x 10 6 cells / ml and 7.13 x 10 6 cells / mlrespectively. the highest protein content of Nannochloropsis oculata was produced at nitrate concentration of 200 g/L amount of 25.74% and 25 g/L phosphate consentration of amount 22.93%. Key words: biomass, Nannochloropsis oculata, protein, Walne.
Keywords: 128,